Analisis terhadap Enkripsi Data SSL di MySQL: Menguji Keamanan In-Transit - Haikal, Antoni; Putra, Septafiansyah Dwi; Nelmiawati, Nelmiawati (ROUTERS: Jurnal Sistem dan Teknologi Informasi, 2024)
Data transmission security has become a pivotal point in database management, especially in response to the evolving cyber threats. This study examines a critical aspect of data security: the in-transit data encryption using Secure Sockets Layer (SSL) within MySQL. The main focus of the research is on testing data encryption by employing Wireshark, a network analysis tool capable of capturing and displaying transmitted data packets. The testing process consisted of two scenarios: first, data transmission with SSL enabled on the MySQL server; second, data transmission without the use of SSL. The results show a significant contrast between the two scenarios. With SSL, the data packets intercepted by Wireshark appeared unreadable, indicating that encryption was successful in preventing data content exposure. Conversely, without SSL, the data packets could be read as plain text, demonstrating a lack of encryption and a high security risk. This research delves only into the aspect of in-transit data encryption security in MySQL and does not explore the implications related to SSL performance or configuration further. This analysis offers a useful perspective for database administrators in efforts to enhance data security, identifying SSL as a crucial tool to ensure the security of in-transit data.